Static Adsorption, by Activated Carbons, of Vapour Mixtures Corresponding to Immiscible Liquids - D. Wintgens; A. Lavanchy; F. Stoeckli (Adsorption Science & Technology)
It is shown that the static adsorption of benzene and water vapours by a typical industrial active carbon can be described by the model of independent co-adsorption proposed for compounds which are not miscible in the liquid state. The model assumes that the vapours are adsorbed according to their respective DA isotherms, each component using the micropore volume left unoccupied by the other. A good agreement is found between the calculated and the experimental adsorption, but in the case of water the model must take into account the decrease of the characteristic energy E(H 2 O) with increasing co-adsorption of benzene. This behaviour is confirmed by earlier studies of water adsorption and of immersion calorimetry into water, following variable pre-adsorption of n-nonane.